2002
DOI: 10.1038/oby.2002.161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High‐Fat Diet and Strain on Hypothalamic Gene Expression in Rats

Abstract: Effects of a high-fat diet and strain on hypothalamic gene expression in rats. Obes Res. 2002;10:1188 -1196. Objective: This study was designed to investigate whether dietary fat and genetic background might differentially alter the expression of hypothalamic genes involved in food intake. Research Methods and Procedures: Three-month-old Osborne-Mendel (OM) and S5B/Pl rats were fed either a high-fat or a low-fat diet for 14 days. mRNA for neuropeptide Y (NPY), corticotrophin-releasing hormone, NPY Y-1 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…HTR2C density and mRNA have been found to increase in the hypothalamus of mice on high-fat diets (Huang et al 2004), in response to low 5-HT concentrations in the ventromedial hypothalamus nucleus (VHM). Increases in leptin but a reduction in HTR2C mRNA in the hypothalamus have also been observed in high-fat diets (Schaffhauser et al 2002). In rats, leptininduced anorexia and milk intake was attenuated by the HTR2C antagonists SB242084 and SB206553, respectively (von Meyenburg et al 2003;Yamada et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…HTR2C density and mRNA have been found to increase in the hypothalamus of mice on high-fat diets (Huang et al 2004), in response to low 5-HT concentrations in the ventromedial hypothalamus nucleus (VHM). Increases in leptin but a reduction in HTR2C mRNA in the hypothalamus have also been observed in high-fat diets (Schaffhauser et al 2002). In rats, leptininduced anorexia and milk intake was attenuated by the HTR2C antagonists SB242084 and SB206553, respectively (von Meyenburg et al 2003;Yamada et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…The Osborne-Mendel rat is one of these DIO-S rats. Its NPY mRNA expression is about 50% higher than in S5B/P1 rats (Schaffhauser et al 2002). Despite this increase, Y1 and Y5 mRNA expression is raised by 16-71% with the highest augmentation measured on a LF diet (Schaffhauser et al 2002).…”
Section: Npy In Diet-induced Obesity (Dio)mentioning
confidence: 99%
“…Intriguingly, it has recently been reported that the anorexinergic effect of a new HTR2C agonist, BVT.X, is strictly associated with the activity of the melanocortin receptor 4 in the arcuate nucleus of the hypothalamus, and that HTR2C is coexpressed with neurons containing pro-opiomelanocortin [Lam et al, 2008]. Along with this, the role of HTR2C in the energy balance control has been widely demonstrated: a diet enriched in fat content was found to be associated with a downregulation of the HTR2C mRNA expression in rats [Schaffhauser et al, 2002], and the anorexinergic properties of lipopolysaccharide, IL-1 and leptin were shown to be under the control of HTR2C [von Meyenburg et al, 2003]. Moreover, HTR2C knock out animals show enhanced risk to develop obesity and impaired glucose homeostasis [Tecott et al, 1995;Wang and Chehab, 2006;Wade et al, 2008], and, intriguingly, it has been demonstrated that this is more evident after multiple stresses [Chou-Green et al, 2003].…”
mentioning
confidence: 94%